2016
DOI: 10.1016/j.cub.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Loss and Re-emergence of Legs in Snakes by Modular Evolution of Sonic hedgehog and HOXD Enhancers

Abstract: Limb reduction and loss are hallmarks of snake evolution. Although advanced snakes are completely limbless, basal and intermediate snakes retain pelvic girdles and small rudiments of the femur. Moreover, legs may have re-emerged in extinct snake lineages [1-5], suggesting that the mechanisms of limb development were not completely lost in snakes. Here we report that hindlimb development arrests in python embryos as a result of mutations that abolish essential transcription factor binding sites in the limb-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
153
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 37 publications
2
153
2
Order By: Relevance
“…Earlier work suggested that the limb fails to grow because of a degeneration of the AER resulting in the lack of Fgf and Shh production breaking the ectodermal-mesenchymal Fgf positive feedback loop (Cohn and Tickle, 1999). Recently, however, it was been discovered that pythons do initially induce Shh and Fgf8 in early hindlimb buds, only transiently and Shh expression is reduced due to degeneration of the ZRS (Kvon et al, 2016; Leal and Cohn, 2016). Further analysis revealed that a conserved Ets1 binding site in the ZRS is lost in all examined snake genomes and restoration of this site is sufficient to rescue the full activity of the ZRS (Kvon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work suggested that the limb fails to grow because of a degeneration of the AER resulting in the lack of Fgf and Shh production breaking the ectodermal-mesenchymal Fgf positive feedback loop (Cohn and Tickle, 1999). Recently, however, it was been discovered that pythons do initially induce Shh and Fgf8 in early hindlimb buds, only transiently and Shh expression is reduced due to degeneration of the ZRS (Kvon et al, 2016; Leal and Cohn, 2016). Further analysis revealed that a conserved Ets1 binding site in the ZRS is lost in all examined snake genomes and restoration of this site is sufficient to rescue the full activity of the ZRS (Kvon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in snakes, this enhancer is only active in the genital tubercle (Infante et al, 2015). Interestingly, the cis-regulatory modules that control the early and late phase Hox expression in tetrapod limbs is conserved in pythons suggesting that they retain the ability to properly pattern the proximodistal axis of their diminutive limbs (Leal and Cohn, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Kvon et al [2016] demonstrated that through nucleotide-specific changes in the zone of polarizing activity regulatory sequence (ZRS, which is a limb-specific enhancer of Sonic hedgehog) in snakes the ZRS enhancer has progressively lost its function during snake evolution, leading to the disappearance of the limbs. In contrast, according to Leal and Cohn [2016], Hoxd limb enhancers are conserved in the python embryo. Expression of Hoxd13 spreads throughout the distal region of the python hind limb bud, overlapping with Hoxa13 expression in a pattern that resembles digitforming domains of Hoxa13 and Hoxd13 in limbed tetrapods [Montavon et al, 2011].…”
Section: Hox Genes In Reptile Developmentmentioning
confidence: 99%
“…Expression of Hoxd13 spreads throughout the distal region of the python hind limb bud, overlapping with Hoxa13 expression in a pattern that resembles digitforming domains of Hoxa13 and Hoxd13 in limbed tetrapods [Montavon et al, 2011]. Therefore, because Hoxd expression in digits and external genitals are under shared regulatory control, it is possible that Hoxd distal enhancers were retained in snakes due to their essential role in external genital development [Lonfat et al, 2014;Leal and Cohn, 2016].…”
Section: Hox Genes In Reptile Developmentmentioning
confidence: 99%
See 1 more Smart Citation